Educational practices at the Faculty of Philosophy in Zagreb – further steps towards student-centered learning - Lasić-Lazić, Jadranka (Array, 2005)
The paper analyses and defines a range of international and global trends, with particular reference to the Croatian context. Therefore special attention will be given to the concept of blended learning, which not only represents the thoughtful integration of classroom face-to-face learning experiences with online learning experiences consolidating the advantages of both traditional and e-learning approaches, but also constitutes a necessary transitional step towards a more comprehensive ICT application in education.